Perbedaan Tingkat Self Esteem Antara Siswa Jurusan IPA dan IPS Di MA Mu’allimien Muhammadiyah Kabupaten Bogor - Nurul Fanisa; Sigit Muryono (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The aim of this research is to compare the level of Self Esteem between students from the Science (IPA) and Social Sciences (IPS) majors at MA Mu’allimien Muhammadiyah Bogor. This study utilized a comparative study design with a quantitative approach. The sample consisted of 21 students from the IPA major and 43 students from the IPS major, selected through purposive sampling. The research data were analyzed using independent sample t-tests with the assistance of SPSS Ver.26 software. The results of the analysis showed a significance value of 0.002 < 0.05, indicating the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). This suggests that there is a significant difference in the level of self esteem between students from the IPA and IPS majors in the school. Furthermore, students from the IPA major demonstrated a higher level of self esteem, with a mean score of 23.10, while students from the IPS major had a mean score of 17.53. Therefore, it can be concluded that students from the IPA major exhibit a higher level of self esteem compared to students from the IPS major in the school.